The Complexity of Piroplasms Life Cycles - Jalovecka, Marie; Hajdusek, Ondrej; Sojka, Daniel; Kopacek, Petr; Malandrin, Laurence (Frontiers in Cellular and Infection Microbiology, 2018)
Although apicomplexan parasites of the group Piroplasmida represent commonly identified global risks to both animals and humans, detailed knowledge of their life cycles is surprisingly limited. Such a discrepancy results from incomplete literature reports, nomenclature disunity and recently, from large numbers of newly described species. This review intends to collate and summarize current knowledge with respect to piroplasm phylogeny. Moreover, it provides a comprehensive view of developmental events of Babesia, Theileria and Cytauxzoon representative species, focusing on uniform consensus of three consecutive phases: (i) schizogony and merogony, asexual multiplication in blood cells of the vertebrate host; (ii) gamogony, sexual reproduction inside the tick midgut, later followed by invasion of kinetes into the tick internal tissues; and (iii) sporogony, asexual proliferation in tick salivary glands resulting in the formation of sporozoites. However, many fundamental differences in this general consensus occur and this review identifies variables that should be analyzed prior to further development of specific anti-piroplasm strategies, including the attractive targeting of life cycle stages of Babesia or Theileria tick vectors.